2010
DOI: 10.1115/1.4001006
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Effect on a Cavitating Inducer—Part I: Geometrical Similarity of Leading Edge Cavities and Cavitation Instabilities

Abstract: International audienceThe thermodynamic effect on a cavitating inducer is investigated from joint experiments in cold water and Refrigerant 114. The analysis is focused on leading edge cavitation and cavitation instabilities, especially on alternate blade cavitation and supersynchronous rotating cavitation. The cavity length along cylindrical cuts at different radii between the hub and casing is analyzed with respect to the local cavitation number and angle of attack. The similarity in shape of the cavity clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In Eq. 20 , the first term represents the suppression effect coming from (1) the pressure term, i.e., the square of , which is based on the classical second-order cavity length law [21] , and (2) the turbulent term, i.e., the reciprocal of [43] , which is scaled by dividing Re by to be of the same order as *. In addition, the tangent function is used to amplify the effect of the first term based on experimental observation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eq. 20 , the first term represents the suppression effect coming from (1) the pressure term, i.e., the square of , which is based on the classical second-order cavity length law [21] , and (2) the turbulent term, i.e., the reciprocal of [43] , which is scaled by dividing Re by to be of the same order as *. In addition, the tangent function is used to amplify the effect of the first term based on experimental observation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consequently, substantial evaporative cooling effects occur surrounding the cavity in water, and a few degrees temperature difference can be expected between the liquid bulk and cavitating region. Thus, a delay of cavitation can be expected due to the temperature difference between the mainstream liquid and local cavity area, i.e., the thermodynamic effect [21] .…”
Section: Introductionmentioning
confidence: 99%
“…This effect is required to be take into account in cavitation in cryogenic liquids, refrigerant and high temperature water, where the working temperature is close to the critical point temperature of the liquids. In order to investigate the influence of the thermodynamic effect, cavitation experiments have been carried out using the above mentioned liquids [3][4][5][6][7][8][9]. In contrast to the theoretical inference, a number of experimental studies found that a stronger thermodynamic effect enhances the degree of the sheet/cloud cavitation in some cases, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large variety of modelling, the numerical simulation of cavitating flow in thermosensitive liquids remains a challenge. Experimentally, for cryogenic and refrigerant fluids, numerous previous works have proved the settling of thermal gradients in the vicinity of cavitating flows [40,41,42,43,44,45,46]. Recent progress in non intrusive temperature measurement in diphasic flow have brought new insights in the field of heat transport in cavitating flow.…”
Section: Introductionmentioning
confidence: 99%